Pengembangan perangkat pembelajaran berbasis inkuiri untuk meningkatkan kemampuan berpikir kritis dan tanggung jawab siswa pada pembelajaran tematik integratif - Marlina, Amalia Dwi; Sugito, Sugito (Graduate School, Universitas Negeri Yogyakarta, 2018)
Penelitian ini bertujuan untuk menghasilkan Perangkat Pembelajaran Tematik Integratif Berbasis Inkuiri yang layak untuk meningkatkan kemampuan berpikir kritis dan tanggung jawab siswa serta menguji keefektifan perangkat pembelajaran yang dihasilkan. Jenis penelitian ini adalah penelitian dan pengembangan (RD). Desain penelitian yang digunakan mengacu pada desain Borg Gall, yaitu: (1) research and information collection, (2) planning, (3) develop preliminary form of product, (4) preliminary field testing, (5) main product revision, (6) main field testing ,(7) operational product revision, (8) operational field testing, (9) final product revision, dan (10) dissemination and implementation. Subjek penelitian adalah siswa dan guru kelas IV SD N Grindang, SD N Pucanggading, SD N Gunung Agung, dan SD N Sangon. Data diperoleh melalui wawancara, observasi, angket, dan tes. Hasil penelitian menunjukkan bahwa: (1) Perangkat pembelajaran tematik integratif berbasis inkuiri yang dihasilkan layak untuk meningkatkan kemampuan berpikir kritis dan tanggung jawab siswa, (2) Perangkat pembelajaran yang dihasilkan efektif untuk meningkatkan kemampuan berpikir kritis dan tanggung jawab siswa.Kata kunci: perangkat pembelajaran tematik integratif, inkuiri, kemampuan berpikir kritis, tanggung jawab DEVELOPING AN INQUIRY-BASED LEARNING KIT FOR IMPROVING THE CRITICAL THINKING ABILITY AND RESPONSIBILITY ON INTEGRATIVE THEMATIC LEARNING AbstractThis study aims to produce an inquiry-based integrative thematic learning kit for improve the critical thinking skills and responsibility of students and to reveal the effectiveness of the developed learning kit. This research was research and development (R D). The research design used the design of Borg Gall, namely: (1) research and information gathering, (2) planning, (3) developing initial product forms, (4) preliminary field testing, (5) product revisions main, (6) main field testing, (7) revision of operational products, (8) operational field trials, (9) final product revisions, and (10) dissemination and implementation. The subjects were the fourth grade students and teachers of State Elementary School SD N Grindang, SD N Pucanggading, SD N Gunung Agung, and SD N Sangon. The data were obtained through interviews, questionnaires, and tests. The results are as follow (1) the developed inquiry-based integrative thematic learning kit can be used to improve critical the thinking skills and responsibility of student, (2) The developed learning kit is effective in improving the student critical thinking skills and responsibility.Keywords: integrative thematic learning devices, inquiry, critical thinking skills, responsibility